2018
DOI: 10.1155/2018/4137943
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adjuvant Radiotherapy for a Case of Primary Breast Sarcoma: A Plan Comparison between Three Modern Techniques and a Review of the Literature

Abstract: A 65-year-old woman, affected by a malignant fibrous histiocytoma (undifferentiated pleomorphic sarcoma) of the left breast, presented to our department to receive the postoperative radiotherapy. In the absence of prospective and randomized trials and investigations on breast sarcoma irradiation in literature, due to the rarity of this pathology, the role of adjuvant radiotherapy remains unclear. To identify the best radiotherapy technique for this patient, three methods were compared: 3D conformal radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…Considering the risk of recurrence and metastasis, we suggested adjuvant chemotherapy after total mastectomy. Adjuvant radiotherapy ( 14 , 22 ) or chemotherapy ( 18 ) for patients with breast UPS, has been reported only in a few cases and the most appropriate treatment strategy has remained uncertain and needs to be explored using further cases. Sufficient excision of the primary breast tumor with free-of-tumor margins would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the risk of recurrence and metastasis, we suggested adjuvant chemotherapy after total mastectomy. Adjuvant radiotherapy ( 14 , 22 ) or chemotherapy ( 18 ) for patients with breast UPS, has been reported only in a few cases and the most appropriate treatment strategy has remained uncertain and needs to be explored using further cases. Sufficient excision of the primary breast tumor with free-of-tumor margins would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low number of patients is likely partly responsible for this result [ 25 ]. Finally, when administering adjuvant RT to patients MPNS sarcomas of the breast, the treatment must ensure an efficient target area of coverage with high doses, generally between 50 and 60 Gy, to guarantee better local control [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our case demonstrated that with a missed diagnosis, within 6 months, tumour size can more than double. Adjuvant radiation and chemotherapy may benefit patients with high-grade features 17 38. Although there have been limited studies on biological markers as prognostic factors, high Ki-67 has been shown to be a poor prognostic factor that is associated with higher risk of local recurrence, distant metastasis and poor prognosis in primary UPS of the breast 15.…”
Section: Discussionmentioning
confidence: 99%